2005
DOI: 10.1039/b419206k
|View full text |Cite
|
Sign up to set email alerts
|

One-step synthesis of phenol by O– and OH– emission material

Abstract: A novel approach to the direct synthesis of phenol from benzene was obtained with high benzene conversion (30%) and phenol selectivity (approximately 90%) by using a microporous material [Ca24Al28O64]4+.4O-(C12A7-O-) as catalyst with oxygen and water; active O- and OH- anions are proposed to play important roles in the formation of phenol by hydroxylating the aromatic ring of benzene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 23 publications
1
59
0
Order By: Relevance
“…Dong et al reported that a direct oxidation of benzene using C12A7O ¹ yields phenol. 9) Wang et al also reported a production of hydrogen by catalytic steam reforming of bio-oil using C12A7O ¹ . 10) Yang et al reported partial oxidation of methane using C12A7O ¹ .…”
Section: )8)mentioning
confidence: 99%
“…Dong et al reported that a direct oxidation of benzene using C12A7O ¹ yields phenol. 9) Wang et al also reported a production of hydrogen by catalytic steam reforming of bio-oil using C12A7O ¹ . 10) Yang et al reported partial oxidation of methane using C12A7O ¹ .…”
Section: )8)mentioning
confidence: 99%
“…The C12A7-O -sample was prepared by a solid-state reaction at 1623 K for 16 h. The more detailed process for preparation can be found elsewhere [22,23,38,39]. The C12A7-O -pellet was powdered and mechanically mixed with various content of K 2 CO 3 .…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…For example, C12A7 has been used as a catalyst mainly in the pyrolysis of n-hexane [31], n-heptane [32][33][34], methylcyclohexane [35] and partial oxidation of methane [36,37]. More recently, we found the C12A7-O -catalyst was active in hydroxylation of benzene [38] and steam reforming of bio-oil [39].…”
Section: Introductionmentioning
confidence: 99%
“…Many 176 Liquid-phase oxidation reactions of benzene with molecular oxygen have been reported on an iron-heteropolyacid catalyst and a CuO/Al 2 O 3 catalyst with ascorbic acid as a reducing reagent. 148,149 A Cu/ ZSHM-5 catalyst showed a maximum phenol selectivity of 60% with a phenol yield of 1.2% at 673 K. 150 However, the selective oxidation of benzene using O 2 was nominated as one of the ten most difficult challenges in catalysis 177179 and indeed there have been no reports on direct remarkable catalysts for phenol synthesis with performance greater than 5% benzene conversion and 50% phenol selectivity over the last 50 years.…”
Section: Tadamentioning
confidence: 99%